HUBUNGAN MOTIVASI KERJA DENGAN KINERJA KARYAWAN PADA PT KAO INDONESIA - Jaya, Indra; Ningsih, Surya (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2016)
ABSTRACTMotivation has a close relationship and how a persons behavior begins, supported, strengthened and redirected. Therefore the basis for motivating employees, among others, is to create a work atmosphere that can cause or make employees can act and do something. Basically the employees performance is the result of a complex process, both derived from the employees personal self (internal factors) as well as the strategic efforts of the company through a leader, one of the ways of enhancing the sake of achieving good performance is to provide motivation or encouragement. This study aimed to clarify whether there is a relationship work motivation and performance of employees at PT Kao Indonesia.Hasil analysis Pearson product moment correlation coefficient correlation of 0.540 means that work motivation and performance of employees have a relationship that was. Determination coefficient of 29.16% means that employee performance variation can be explained by the work motivation of 29.16% and the remaining 70.84% is explained by other factors not examined. Hypothesis test results correlated with t test showed tcount > ttable (4.889> 2.002) H0 is rejected it means there is a real relationship between work motivation and employee performance.Keywords: Motivation and Employee Performance